DNA Bar-coding: A Novel Approach for Identifying an Individual Using Extended Levenshtein Distance Algorithm and STR analysis - Likhitha C P; Ninitha P; Kanchana V (Institute of Advanced Engineering and Science, 2016)
DNA bar-coding is a technique that uses the short DNA nucleotide sequences from the standard genome of the species in order to find and group the species to which it belongs to. The species are identified by their DNA nucleotide sequences in the same way the items are recognized and billed in the supermarket using barcode scanner to scan the Universal Product Code of the items. Two items may look same to the untrained eye, but in both cases the barcodes are distinct. It was possible to create DNA-barcodes to characterize species by analysing DNA samples from fish, birds, mammals, plants, and invertebrates using Smith-waterman and Needleman-Wunsch algorithm. In this work we are creating human DNA barcode and implementing Extended Levenshtein distance algorithm along with STR analysis that uses less computation time compared to the previously used algorithms to measure the differential distance between the two DNA nucleotide sequences through which an individual can be identified.